Factors Associated with Medication Adherence in Hypertensive Patients in Rural Areas - Hella Tursina; Achmad Sya'id; Anita Fatarona (Jurnal Kesehatan dr. Soebandi, 2024)
Hypertension can have significant impacts if not addressed promptly, and treatment is often initiated too late. Effective management necessitates integrated care that considers both internal and external factors. Patients actively engaged in their treatment should possess essential qualities, including knowledge and motivation. This study aimed to investigate the factors associated with medication adherence in hypertensive patients residing in the rural area of Jember City. Using a cross-sectional design, this study focused on hypertensive patients in rural Jember. A simple random sampling technique was employed, including 94 respondents. Data collection was conducted using a questionnaire, with analysis performed using the Chi-Square test. The statistical results indicated a p-value of 0.015 (p < α = 0.05), suggesting that the level of knowledge is associated with medication adherence. Additionally, motivation yielded a result of p = 0.02 (p < α = 0.05), indicating that respondents' motivation correlates with adherence levels. The analysis of healthcare support showed a p-value of 0.048 (p < α = 0.05), demonstrating its association with adherence. Furthermore, family support revealed a p-value of 0.000 (p < α = 0.05), indicating significant influence on adherence levels. The variable concerning complementary therapy also showed a strong relationship, with a p-value of 0.000. In contrast, the type of medication indicated a p-value of 0.485 (p > α = 0.05), suggesting no correlation with adherence. All respondents reported that healthcare facilities were easily accessible.